MENGKRITISI JARINGAN ISLAM LIBERAL (JIL): ANTARA SPIRIT REVIVALISME, LIBERALISME DAN BAHAYA SEKULARISME - Hamdiah A Latif (Universitas Islam Negeri Ar-Raniry, 2011)
This article deals with the development of liberal Islam in Indonesia by concentrating on the group Jaringan Islam Liberal (Liberal Islam Network; henceforward JIL). The term of liberal Islam refers to a trend among a particular group of Muslims who argue that understanding the text of Islamic teachings should be complemented by the context in which it is being reinterpreted because the text does not exhaust all the meanings of the revelation. This group also spreads basic ideas such as the opening of the gates of ijtihad, stressing the spirit of religious ethics, pluralism and relativism, the support of minorities and religious freedom. The presence of this group has aroused many responses to the ideas that it promotes. One of the responses and critics is inadequate method that JIL used in order to reach an authoritative understanding. Another problem is spirit of Islamic liberalism understanding that used will lead at the last to the idea of secularization, which draws a distinct line between religion and politics.